Screening, Purification And Characterization Of Extracellular Lipase Produced By Pediococcus Acidilactici Ub6 Isolated From Malaysian Fermented Foods - Yap, Sia Yen (2007)
The extracellular lipase produced by Lactic Acid Bacteria (LAB) has not been studied extensively, although the intracellular lipolytic capability of LAB isolated from fermented foods has been reported. Thus, the present work was conducted to screen, characterize and purify the extracellular lipase produced by 41 Lactic Acid Bacteria (LAB) isolated from Malaysian fermented foods. The lipase producer was determined by using qualitative and quantitative methods. For qualitative method, all tested LAB isolate demonstrated blue colour colonies on the Nile blue sulphate agar plate. Thus, the extracellular lipase activity of LAB was further quantified by using both titration and spectrophotometric assay methods. All tested LAB isolates exhibited lipolytic activity when assayed with 50 mM Tris-HCl, pH 8.0 buffer with UB6 isolate as the highest extracellular lipase producer. Only 38 isolates of LAB demonstrated lipolytic activity when assayed with 50 mM sodium acetate, pH 4.5 buffer by using titration assay method with GP13 as the highest extracellular lipase producer. However, UB6 was selected for further studies as it exhibited lipolytic activity under both alkaline and acidic assay conditions. The UB6 isolate was designated as Pediococcus acidilactici UB6 based on both phenotypic biochemical tests and API test kit. The optimum alkaline assay condition for titration method was: 150 rpm of agitation, 20 min of incubation time, 5% (w/v) gum Arabic, 500 μl olive oil and 100 μl of cell free supernatant (CFS). The same optimum assay condition was obtained for the spectrophotometric method, except 20 μl of p-NP palmitate and 300 μl of CFS was used in the assay mixture. For the growth study, the maximum production of extracellular lipase was detected after 15 h incubation, which was occurred at the late log phase. The crude extracellular lipase UB6 was characterized on the basis of pH and buffer types, temperatures and substrates specificity. The optimum activity was attained when lipase assay was performed with 50 mM Tris-HCl, pH 8.0 buffer at 37ºC for both titration and spectrophotometric assay methods. However, the optimum temperature was shifted to 40ºC when assayed with 50 mM sodium acetate, pH 5.0 buffer for titration method. Generally, the crude extracellular lipase UB6 exhibited broad substrate affinity. However, the preference was towards the long chain fatty acids. For temperature stability study, the crude extracellular lipase UB6 was able to retain 100% activity after being incubated at 40ºC for 1 h. Conversely, the lipolytic activity decreased dramatically when temperature was above 50ºC. For storage study, the lipolytic activity remained 70% after being kept at –20, 0 and 4ºC for 9 weeks, respectively. However, after being stored at 8, 15, 30 and 37ºC for 9 weeks, the lipolytic activity was remained at 60%, 55%, 50% and 40%, respectively. The lipase activity was not significantly affected by Proteinase K, however, it was affected greatly by β-chymotrypsin, α-chymotrypsin, trypsin, papain and lysozyme. The extracellular lipase UB6 was stable in 0-1% (w/v) NaCl. The extracellular lipase UB6 was purified to apparent homogeneity by using 4 steps purification procedure comprising of 0-100% ammonium sulphate precipitation, anion-exchange Source 30 Q chromatography, packed Superose 12 gel filtration chromatography and Concanavilin A (Con-A) affinity chromatography. The extracellular lipase UB6 was successfully purified to apparent homogeneity with 3.23% overall recovery and 136 purification fold. The molecular mass of both purified unbound and bound Con-A lipase active fractions was estimated to be 28,155 and 32,000 Da by Superose 12 gel filtration chromatography and Glycine sodium dodecyl sulphate polyacylamide gel electrophoresis, respectively, whereas, the isoelectric points of both lipase active fractions were estimated to be pI 3.5-5.2 (acidic) and pI 8.4 (alkaline). Both purified unbound and bound to Con-A lipase active fractions contained 60% and 71% of hydrophobic amino acids at N-terminal. In addition, the maximal activity for both purified Con-A fractions were detected at pH 4.0 and pH 8.0, respectively. As for substrate affinity, both purified Con-A fractions exhibited higher affinity towards long chain fatty acids.